2015
DOI: 10.1016/j.jhydrol.2015.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Global sensitivity analysis in hydrological modeling: Review of concepts, methods, theoretical framework, and applications

Abstract: s u m m a r y Sensitivity analysis (SA) aims to identify the key parameters that affect model performance and it plays important roles in model parameterization, calibration, optimization, and uncertainty quantification. However, the increasing complexity of hydrological models means that a large number of parameters need to be estimated. To better understand how these complex models work, efficient SA methods should be applied before the application of hydrological modeling. This study provides a comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
273
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 458 publications
(318 citation statements)
references
References 176 publications
0
273
0
2
Order By: Relevance
“…These cases were considered because they sampled realistic errors (NB and NB_gauge) and minimum errors (NB_lab). We expected that the error ranges exerted a major control on model uncertainty and sensitivity, as demonstrated in several prior sensitivity analyses (see review of Song et al, 2015).…”
Section: Error Magnitudesmentioning
confidence: 90%
See 3 more Smart Citations
“…These cases were considered because they sampled realistic errors (NB and NB_gauge) and minimum errors (NB_lab). We expected that the error ranges exerted a major control on model uncertainty and sensitivity, as demonstrated in several prior sensitivity analyses (see review of Song et al, 2015).…”
Section: Error Magnitudesmentioning
confidence: 90%
“…It is unclear how (1) different error types (bias vs. random errors), (2) different error distributions, and (3) different error magnitudes across all forcings affect model output. The impact of forcing errors on models can be tested by corrupting forcings with specified characteristics (e.g., artificial biases and random errors) and quantifying the impact on model outputs (e.g., Oudin et al, 2006;Spank et al, 2013), but we are unaware of any detailed studies that have done this type of experiment for all meteorological forcings commonly required for physically based snow models. We hypothesize that (1) model outputs are more sensitive to biases than random errors in forcing variables, (2) the assumed probability distribution for biases will alter the relative ranking of importance in forcing errors, and (3) the magnitude of forcing biases will have a strong influence on which forcing errors are most important.…”
Section: S Raleigh Et Al: Physical Model Sensitivity To Forcing mentioning
confidence: 99%
See 2 more Smart Citations
“…Nossent et al (2011) reported that for most parameters, less than 5000 samples were sufficient to reach a stable solution. An extensive review of the GSA in hydrological models is reported in Song et al (2015). Here, we report the number of model runs for each GSA performed, together with the type of GSA, the number of parameters of the model, and the objective function used.…”
Section: Global Sensitivity Analysismentioning
confidence: 99%